UNMANNED AIRCRAFT SYSTEMS - ADJUSTMENT OF CROATIAN REGULATION TO THE NEW LEGAL FRAMEWORK OF THE EUROPEAN UNION - Činčurak Erceg, Biljana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Abstract: Unmanned aircrafts are rapidly developing, and their application is ever wider. The number of unmanned aircraft users is increasing, and it is necessary to harmonize the existing legislation at the EU level and to amend the regulatory framework appropriately. The safety and liability of using unmanned aircraft systems are certainly the most important elements to consider. In accordance with the development of new solutions within the European Union, the Republic of Croatia has amended the Ordinance on unmanned aircraft systems of 2015 (Official Gazette, Nos. 49/2015 and 77/2015) in the year 2018 (Official Gazette, No. 104/2018). Although the Croatian Civil Aviation Agency has stated that the main reason for drafting a new Ordinance is to adjust the national system to the future European Union system in order to facilitate the implementation of the new Regulation on unmanned aircraft operations when it enters into force, it is surprising that the Republic of Croatia has decided to amend the Ordinance before the mentioned Regulation is adopted. Especially if we consider that the work on the adoption of the European Regulation lasts for several years. The use of unmanned aircraft systems will be certainly expanded. However, it should be emphasized that the use of unmanned aircrafts is not a game and that the safety rules must be respected. Adjustment of the legal framework to improve it certainly needs to be praised. It remains to be seen what the EU will do and what would be the dynamics when we talk about the regulation of unmanned aircrafts and how the member states will adapt.Key words: unmanned aircraft, Ordinance on unmanned aircraft systems, the Republic of Croatia, European Union, legal regulation